A New Isoflavone and Other Constituents from Roots of Clitoria guianensis - Cunha, Camila L. [UNESP]; Siebeneichler, Susana C.; Nascimento, Isabele R. [UNESP]; Holzbach, Juliana C. (Soc Brasileira Quimica, 2020)
A new isoflavone named pratensein-7-O-beta-D-rutinoside [(-)-7-O-alpha-L-rhamnopyranosyl(1 -> 6)-beta-D-glucopyranosy1-5,3'-dihydroxy-4'-methoxyisoflavone] and the known compounds biochanin A-7-O-beta-D-rutinoside. 6-deoxyclitoriacetal A-O-beta-D-glucopyranoside. 6-deoxyclitoriacetal. (2S)-naringenin-6-C-beta-D-glucopyranoside. (2R)-naringenin-6-C-beta-D-glucopyranoside, tachioside, and koaburaside were isolated from the roots of Clitoria guianensis (Aubl.) Benth var. guianensis (Fabaceae), a subshrub found in the Brazilian Cerrado biome. The structures of the compounds were identified by physical and spectroscopic data measurements (specific rotation ([alpha](D)), circular dichroism (CD), ultraviolet (UV), infrared (IR), 1D and 2D nuclear magnetic resonance (NMR), and mass spectrometry (MS)). The EtOAc fraction of the roots exhibited high toxicity against Anemia salina with median lethal dose (LD50) value of 8.53 mg L-1.
Keywords: Clitoria guianensis; Fabaceae; isoflavone; flavanone